2009
DOI: 10.1080/13550280902973960
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for ongoing brain injury in human immunodeficiency virus–positive patients treated with antiretroviral therapy

Abstract: Treatment with antiretroviral therapy (ART) has greatly reduced the incidence of dementia. The goal of this longitudinal study was to determine if there are ongoing macrostructural brain changes in human immunodeficiency virus-positive (HIV+) individuals treated with ART. To quantify brain structure, three-dimensional T1-weighted magnetic resonance imaging (MRI) scans were performed at baseline and again after 24 months in 39 HIV+ patients on ART and 30 HIV− controls. Longitudinal changes in brain volume were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
107
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(118 citation statements)
references
References 45 publications
10
107
0
1
Order By: Relevance
“…In fact, in vivo cognitive impairment has been associated with postmortem neuropathologic changes 60 and with in vivo evidences at magnetic resonance imaging studies of white matter tract injury consistent with axonal or neuronal loss 61 and gray and white matter brain loss. 62 Other potential explanations of persistent cognitive impairment in patients treated with successful HAART include ongoing viral replication of compartmentalized HIV within the CNS 47 and insufficient penetration of some ARV drugs within the CNS. 9 Moreover, ongoing chronic inflammatory processes within the CNS and vascular factors might also contribute to persistent cognitive impairment in patients treated with HAART.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, in vivo cognitive impairment has been associated with postmortem neuropathologic changes 60 and with in vivo evidences at magnetic resonance imaging studies of white matter tract injury consistent with axonal or neuronal loss 61 and gray and white matter brain loss. 62 Other potential explanations of persistent cognitive impairment in patients treated with successful HAART include ongoing viral replication of compartmentalized HIV within the CNS 47 and insufficient penetration of some ARV drugs within the CNS. 9 Moreover, ongoing chronic inflammatory processes within the CNS and vascular factors might also contribute to persistent cognitive impairment in patients treated with HAART.…”
Section: Discussionmentioning
confidence: 99%
“…One important area of investigation will be the effect of anti-retroviral therapy on the pathologies described above. Studies to date on this issue regularly yield conflicting results [16,25,28,39], and many findings published prior to the HAART (highly active antiretroviral therapy) era have yet to be re-examined in the context of HAART. Additionally, MRI image acquisition and volumetric processing are continually improving, and the use of more sensitive and accurate protocols may confirm or call into question findings of previous studies.…”
Section: Structural Magnetic Resonance Imagingmentioning
confidence: 99%
“…8,9 Despite cART, there is evidence for ongoing neurologic damage that includes persistent astrocyte infection, brain volume loss, inflammation, synaptodendritic damage, and disruptions in white matter integrity. 5,[10][11][12] The mechanisms underlying these residual neuropathologic impairments remain obscure.…”
Section: 2mentioning
confidence: 99%
“…8,9 Despite cART, there is evidence for ongoing neurologic damage that includes persistent astrocyte infection, brain volume loss, inflammation, synaptodendritic damage, and disruptions in white matter integrity. 5,[10][11][12] The mechanisms underlying these residual neuropathologic impairments remain obscure.Several studies have suggested that dysregulations in CNS lipid metabolism may be involved in the pathogenesis of HAND. [13][14][15] In particular, roles for ceramides, sphingomyelins, and cholesterol have been described, but the interrelationships of these bioactive lipids to the temporal progression *These authors contributed equally to this work.…”
mentioning
confidence: 99%